New species of Microlicia (Melastomataceae) from the Espinhaço Meridional and Septentrional of Minas Gerais, Brazil - Almeda, Frank; Pacifico, Ricardo (Phytotaxa, 2023)
Microlicia rosanae and M. septentrionalis are described as new species from campo rupestre in the Espinhaço Meridional and Septentrional of Minas Gerais, Brazil, respectively. Diagnostic illustrations, field photographs, a distribution map, recommended conservation assessments, and discussions of putative related species based on morphological similarities are provided. Microlicia rosanae, from Serra do Caraça, can be recognized by its sessile oblong to narrowly oblanceolate 1-nerved leaf blades that are revolute when dry, 5–6-merous solitary flowers, hypanthia that are copiously covered with a mixture of inconspicuous spreading short and longer (some gland-tipped) trichomes that are up to ca. 0.25 mm long, fruiting hypanthia that are conspicuously constricted into a short neck just below the torus, and 5–6-locular ovaries that are ca. ½ inferior. Microlicia septentrionalis, from Pico da Formosa in northern Minas Gerais, is readily recognized by its ovate-lanceolate leaves that are somewhat concave when fresh and have red callose-thickened margins, petals pink throughout with an asymmetrical red band on the abaxial surface, hypanthia (at anthesis) somewhat constricted distally above the ovary just below the torus into a neck 1–2.5 mm long, glabrous basally and distally with a sparse ring (sometimes interrupted) of gland-tipped trichomes mostly 0.5 mm long just below the constricted neck, and 5-locular ovaries that are 2/3 inferior and beset with glandular trichomes (up to 0.5 mm long) apically around the base of the style. Microlicia rosanae is compared to the superficially similar M. pilosa and M. septentrionalis is compared with M. mellobarretoi, M. gentianoides, and M. punctata. Both newly proposed species are known only from their respective type localities.